Genesis and Consolidation of the National States of England and France 16th to 17th Centuries - Testi, Dario (Mediterranean Journal of Social Sciences, 2012)
This article is the result of research into the genesis and evolution of the modern state in England and France between theend of the Middle Ages and the close of the 17th century, in a Europe ripped apart by religious wars and dynastic crises, a Europe in themidst of the colonial â€˜adventureâ€™, torn between scientific and philosophical development and religious obscurantism. During a time whendecisions by Popes end one war and start another, when Paris is well worth a mass and sometimes not, when the Turks threatenCatholic Europe from the East and when the Hapsburgs rule an empire where â€œthe sun never setsâ€, new powers rise from the ashes ofthe former giants of Europe, with the small United Provinces, densely populated France and insular England fighting the Crowns ofSpain and Portugal and their respective professional armies for the dominion of the world. From an examination of macro-systemic andspecific studies by current day professors, which focus primarily on economic and political issues but also on social and military matters,I have tried to present a clear, chronological reconstruction of how Valois, the Tudors, the Stuarts and the English revolution contributedto the creation of the national monarchy and the evolution of the idea of the state, a state which at the dawn of the 16th century is theprivate concern of the king and his circle of aristocratic warlords, and which, by the end of the 17th century, is governed by tried andtested bureaucratic systems